2016
DOI: 10.1016/j.electacta.2016.02.034
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Monitoring of Local Corrosion Process of Scratched Epoxy Coated Carbon Steel in Simulated Pore Solution Containing Varying percentage of Chloride ions by Localized Electrochemical Impedance Spectroscopy

Abstract: The present work focuses on the corrosion behaviour of scratched epoxy coated carbon steel in simulated pore solution (SPS) containing varying % of chloride ions (added as NaCl) by localized electrochemical impedance spectroscopy (LEIS). LEIS results indicate that the |Z| at the scratch is decreased significantly with an increase in % of Clions in SPS, which is evidenced by the formation of a depressed semicircle in the LEIS Nyquist plots. The intermediate corrosion products involved in the local corrosion pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…Figures 8(a)-(b) show the MAO-coated AA’s LEIS 3 D maps of 0.5 and 24 h immersions, respectively. As discussed by Balusamy and Nishimura, LEIS 3 D map provides important information on the electrode stability at various individual points (Balusamy and Nishimura, 2016). Moreover, it should be noted that, only the LEIS results from the center area (a ∼5-mm-diameter circle) of the scanned region (10 × 10 mm 2 ) represents the true results of the sample without negligible influence from the surrounding epoxy (Balusamy and Nishimura, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Figures 8(a)-(b) show the MAO-coated AA’s LEIS 3 D maps of 0.5 and 24 h immersions, respectively. As discussed by Balusamy and Nishimura, LEIS 3 D map provides important information on the electrode stability at various individual points (Balusamy and Nishimura, 2016). Moreover, it should be noted that, only the LEIS results from the center area (a ∼5-mm-diameter circle) of the scanned region (10 × 10 mm 2 ) represents the true results of the sample without negligible influence from the surrounding epoxy (Balusamy and Nishimura, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported that chloride ions and oxygen molecules, serving as reactive species during reduction, accelerated the corrosion process based on EDS spectra of the corroded Cr–steel surfaces. Balusamy and Nishimura also studied scratched surfaces and noted that abraded epoxy on top of carbon steel resulted in a decrease in | Z | due to an accumulation of intermediate corrosion products as opposed to decreased | Z | from water-induced adhesion loss.…”
Section: Discussionmentioning
confidence: 99%
“…炭素鋼は優れた機械性能を有し,低価格のため幅広い分 野において使用されている。しかし,パイプライン,貯水 設備および橋梁などの構造物において炭素鋼が激しく腐食 することが報告されている [1][2][3][4] 。炭素鋼の耐食性は表面に 生成された不働態皮膜の安定性によって影響を受ける。こ の不働態皮膜は,塩化物イオンを含む溶液中で容易に破壊 され [5][6][7] ,腐食する。炭素鋼の腐食速度と溶液中の塩化物イ オン濃度に相関があることが報告されている 7,8) 。このこと から,塩化物イオン濃度が同じなら炭素鋼の腐食速度に大 きな差はないと考えられるが,塩化物イオン濃度が同じで も実際の環境において有意な差があることが報告されてい る 9,10) 。 実環境には,塩化物イオンなどのアニオン以外に異なる 金属カチオンが存在している。その影響により腐食速度に 差が生じたと推測できる。Kato ら 11) は,希薄 NaCl 水溶液中 に微量に存在する Al 3 + が炭素鋼の腐食を抑制することを 報告している。Collazo ら 12) は,Mg 2 + が塩化物イオンを含 む環境中で AA2024-T3 の腐食を抑制することを報告して いる。Prabakaran ら 13) は,水溶液中に存在する遊離 Zn 2 + が 炭素鋼の腐食挙動を制御することを報告している。近年, HSAB の概念 14) から導かれる金属カチオンの硬さ 15) ,X, に基づいて,異なる金属カチオンの腐食への影響に関する 研究がある。Zhang ら 16) Table 2. Calculated electrochemical impedance parameters of carbon steel after immersion in the solutions.…”
Section: 緒言unclassified